Screening of cucumber (Cucumis sativus L.) cultivars against southern root knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood (Bangladesh Journal of Botany, 2020)
Fourteen cultivars of cucumber were screened for their resistance to the Southern root-knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood in an in planta experiment. The pots were maintained in greenhouse with CRD for 50 days after inoculation. The cultivar DS92-05 induced significant mortality and was rated “moderately resistant (MR)”. This cultivar showed increase in plant growth parameters including vine length. The cultivars DS92-06, Laghman, Sultan and Desitype were moderately susceptible (MS). The cultivar Rehan and DS96-299 were rated susceptible (S) whereas DS97-299, Chaiya, Beitalpha, Alto, DS92-04 and Local were rated as highly susceptible (HS). DS92-05 is thus promising for sustainable agriculture, specially in those areas with high population density of Southern Root knot nematode.